Pengaruh Return on Equity (ROE), Net Profit Margin (NPM), dan Earning Per Share (EPS) terhadap Harga Saham Perusahaan Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Rikki Yohanes Maitimu; Trisnia Widuri; Ririn Wahyu Arida (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the effect of ROE, NPM, EPS on share prices. This type of research is quantitative research. This research data was obtained through secondary data. The population in this study are all telecommunications companies listed on the IDX 2018-2022. The sample in this research was 30 financial reports. The sampling technique uses purposive sampling. The analysis techniques used are classical assumption tests, panel data regression analysis and hypothesis testing. The research results show that the partial t test results of the ROE variable have a negative and insignificant effect on stock prices, NPM has a positive and significant effect on stock prices. EPS has a negative and insignificant effect on share prices. The results of the F test simultaneously ROE, NPM and EPS have a positive and significant effect on stock prices.